High-chlorine-adsorbing activated carbon, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202610838490.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-11
AI Technical Summary
然而,金属负载法往往面临活性组分分布不均匀、与碳基体结合力弱、在水流冲刷下容易脱落等问题,不仅导致性能衰减,还可能引入金属离子的二次污染风险
[0006] The advantages of the preparation method of high residual chlorine adsorption activated carbon of the present invention are: (1) Amino acids provide nitrogen source and carbon skeleton ligand at the same time, and organic acid iron salts provide iron center. The two can form complexes with iron ions through amino and carboxyl groups to ensure the tight binding of iron and nitrogen. The complexes can be efficiently converted into Fe-NC active sites during subsequent carbonization, avoiding the defects of weak binding force and uneven distribution of metal and carbon matrix in the traditional post-loading method. (2) The temperature of the secondary carbonization stage is relatively lower than the activation temperature. Fe-NC active sites are formed in the secondary carbonization stage, which is conducive to the formation and fixation of Fe-NC structure. The subsequent steam activation is carried out at a higher temperature, which mainly acts on the carbon matrix itself to develop micropore and mesopore structure. Since the Fe-NC sites are embedded in the carbon skeleton, they are relatively difficult to be directly oxidized and destroyed by steam during the activation stage, thus achieving a balance between the stability of active sites and the degree of development of pore structure. (3) The pore-forming agent decomposes and generates gas during the secondary carbonization stage, forming interconnected mesopores and macropores inside the molded body. These channels not only facilitate gas diffusion during subsequent steam activation, but also facilitate the mass transfer of water molecules during the final use of activated carbon, allowing residual chlorine to quickly contact the active sites inside the carbon body, rather than just remaining on the outer surface, thus improving the utilization efficiency of the active sites. (4) After activation, rapid cooling is carried out in an inert atmosphere to avoid oxidation of the high-temperature activated material during the cooling process, effectively protecting the chemical state of the surface reducing active sites and Fe-NC structure, so that they are retained in the final product in a highly active reduced state.
Smart Images

Figure CN122377430B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of water treatment, and more specifically, to high residual chlorine adsorption activated carbon, its preparation method, and its application. Background Technology
[0002] Activated carbon, due to its well-developed pore structure and good chemical stability, is widely used in drinking water purification, especially for removing residual chlorine from water. Residual chlorine (mainly existing in the form of hypochlorous acid and hypochlorite ions) is a residual product of tap water disinfection processes. Although it can inhibit the regrowth of microorganisms, excessive residual chlorine can produce odors and react with organic matter in the water to generate disinfection byproducts. Therefore, it is necessary to effectively remove residual chlorine in the final water purification stage.
[0003] Traditional activated carbon removes residual chlorine primarily through a reduction reaction between the carbon surface and hypochlorous acid. The rate and capacity of this process depend on the number and reactivity of active sites on the activated carbon surface. However, activated carbon prepared by conventional physical or chemical methods has surface active sites dominated by disordered carbon edge defects, resulting in limited reactivity. This leads to rapid residual chlorine penetration during use, making it difficult for the filter cartridge to meet water purification requirements. To extend its lifespan, it is usually necessary to increase the activated carbon loading or frequently replace the filter cartridge, which not only increases costs but also restricts the miniaturization design of the filter cartridge.
[0004] In existing technologies, some studies have attempted to improve the reactivity of activated carbon with residual chlorine by loading metals or doping it with heteroatoms. However, metal loading methods often face problems such as uneven distribution of active components, weak bonding with the carbon matrix, and easy detachment under water erosion, which not only leads to performance degradation but may also introduce the risk of secondary pollution from metal ions. In addition, traditional heteroatom doping methods usually introduce an atmosphere or impregnation solution containing heteroatoms during the high-temperature activation stage. However, the activation process itself aims to create pores, and high temperatures and oxidizing atmospheres can easily destroy the structure of the already formed heteroatom active sites, resulting in low doping efficiency and making it difficult to simultaneously achieve pore structure development and effective construction of active sites. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a high residual chlorine adsorption activated carbon with simple preparation process, good residual chlorine removal effect, and long service life, as well as its preparation method and application. The technical solution is as follows: A method for preparing high residual chlorine adsorption activated carbon includes the following steps: (1) The primary carbonized material is mixed with amino acids, organic acid iron salts, binder and pore-forming agent and kneaded to form a molded body; (2) The shaped blank is subjected to secondary carbonization to obtain secondary carbonized material; (3) The secondary carbonized material is activated by steam to obtain activated material; (4) The activated material is rapidly cooled in an inert atmosphere, and then washed and dried to obtain the high residual chlorine adsorption activated carbon.
[0006] The advantages of the preparation method of high residual chlorine adsorption activated carbon of the present invention are: (1) Amino acids provide nitrogen source and carbon skeleton ligand at the same time, and organic acid iron salts provide iron center. The two can form complexes with iron ions through amino and carboxyl groups to ensure the tight binding of iron and nitrogen. The complexes can be efficiently converted into Fe-NC active sites during subsequent carbonization, avoiding the defects of weak binding force and uneven distribution of metal and carbon matrix in the traditional post-loading method. (2) The temperature of the secondary carbonization stage is relatively lower than the activation temperature. Fe-NC active sites are formed in the secondary carbonization stage, which is conducive to the formation and fixation of Fe-NC structure. The subsequent steam activation is carried out at a higher temperature, which mainly acts on the carbon matrix itself to develop micropore and mesopore structure. Since the Fe-NC sites are embedded in the carbon skeleton, they are relatively difficult to be directly oxidized and destroyed by steam during the activation stage, thus achieving a balance between the stability of active sites and the degree of development of pore structure. (3) The pore-forming agent decomposes and generates gas during the secondary carbonization stage, forming interconnected mesopores and macropores inside the molded body. These channels not only facilitate gas diffusion during subsequent steam activation, but also facilitate the mass transfer of water molecules during the final use of activated carbon, allowing residual chlorine to quickly contact the active sites inside the carbon body, rather than just remaining on the outer surface, thus improving the utilization efficiency of the active sites. (4) After activation, rapid cooling is carried out in an inert atmosphere to avoid oxidation of the high-temperature activated material during the cooling process, effectively protecting the chemical state of the surface reducing active sites and Fe-NC structure, so that they are retained in the final product in a highly active reduced state.
[0007] As a further improvement to the above preparation method, the primary carbonized material is obtained by carbonizing bamboo under air-isolated conditions followed by crushing. The carbonization temperature is 500-650℃, the carbonization time is 2-4 hours, and the particle size is 100-200 mesh. Therefore, the primary carbonized material obtained from bamboo at this carbonization temperature range has a low volatile matter content, and crushing it to 100-200 mesh ensures uniform mixing of the components during subsequent molding, which is beneficial for the uniform distribution of active sites.
[0008] As a further improvement to the above preparation method, the amino acid is selected from at least one of L-lysine, L-arginine, and L-histidine; the organic ferric salt is selected from at least one of ferrous gluconate, ferric ammonium citrate, and ferrous fumarate; the organic ferric salt is pre-added to the aqueous solution of the amino acid, stirred and reacted at 40-60°C for 30-60 minutes, and then mixed with the primary carbonization material. Thus, the selected amino acid contains multiple amino groups or nitrogen-containing heterocycles, has strong coordination ability, and forms a stable complex precursor with the organic ferric salt through pre-reaction, ensuring that iron and nitrogen are simultaneously converted to Fe-NC active sites during carbonization.
[0009] As a further improvement to the above preparation method, the amino acid concentration in the aqueous solution is 4-10 wt%, and the amount of aqueous solution added is 20-30% of the mass of the primary carbonized material; the amount of the organic acid iron salt added is calculated as 0.5-3% of the mass of the primary carbonized material based on iron element. Therefore, within this range, the amino acid concentration and iron salt dosage can provide sufficient nitrogen and iron sources to form adequate active sites without clogging the pores or reducing the carbon content due to excessive doping.
[0010] As a further improvement to the above preparation method, the binder is selected from at least one of starch solution, sodium carboxymethyl cellulose solution, and sodium alginate solution; the amount of binder added is calculated based on the solute being 0.5-3% of the mass of the primary carbonized material. Preferably, the concentration of the starch solution is 5-10 wt%, the concentration of the sodium carboxymethyl cellulose aqueous solution is 2-5 wt%, and the concentration of the sodium alginate aqueous solution is 3-6 wt%. Thus, the natural polymer binder, at this ratio, imparts sufficient molding strength to the green body, and after high-temperature carbonization, it is converted into carbon without introducing harmful residues.
[0011] As a further improvement to the above preparation method, the pore-forming agent is a bicarbonate that decomposes upon heating to produce gas, selected from at least one of sodium bicarbonate and potassium bicarbonate; the particle size of the pore-forming agent is no greater than 48 micrometers; and the amount of the pore-forming agent added is 5-15% of the mass of the primary carbonized material. Thus, the fine-particle-size bicarbonate is uniformly dispersed within the green body, the size of the CO2 bubbles generated by thermal decomposition is controllable, forming a uniform mesoporous-macroporous network and improving the connectivity of mass transfer channels.
[0012] As a further improvement to the above preparation method, In step (2), the secondary carbonization is carried out under air-isolated conditions, with a carbonization temperature of 600-800℃ and a carbonization time of 30-90 minutes; thereby ensuring that Fe-NC sites are fully formed without excessive graphitization. In step (3), the water vapor activation temperature is 850-950℃, and the activation time is 60-180 minutes. This ensures that the micropores develop fully without damaging the already formed active sites.
[0013] As a further improvement to the above preparation method, in step (4), the inert atmosphere is a nitrogen atmosphere, the rapid cooling rate is 50-200℃ / min, and the cooling endpoint temperature is ≤300℃; thus, rapid cooling effectively inhibits the oxidation of active sites at high temperatures; acid washing is performed first, followed by water washing, with 0.1-1mol / L citric acid solution used for acid washing. Thus, citric acid washing gently removes free iron from the surface without damaging the Fe-NC structure embedded in the carbon skeleton, ensuring product safety.
[0014] High residual chlorine adsorption activated carbon is prepared by the above-described preparation method.
[0015] The water purification filter cartridge is filled with the aforementioned high residual chlorine adsorption activated carbon.
[0016] The embodiments of the invention provided in this specification will be further described below with reference to the accompanying drawings and specific embodiments. Additional aspects and advantages of the embodiments of the invention provided in this specification will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the embodiments of the invention provided in this specification. Attached Figure Description
[0017] The accompanying drawings, which form part of the embodiments of the invention provided in this specification, are used to aid in understanding the embodiments of the invention provided in this specification. The content provided in the drawings and the related descriptions in the embodiments of the invention provided in this specification can be used to explain the embodiments of the invention provided in this specification, but do not constitute an undue limitation on the embodiments of the invention provided in this specification. In the drawings: Figure 1 The curve showing the change of residual chlorine concentration over time obtained from the static adsorption experiment of Example 1 is shown.
[0018] Figure 2 The curve showing the change of residual chlorine concentration in the effluent over operating time is obtained from the dynamic adsorption experiment of Example 1. Detailed Implementation
[0019] The embodiments of the invention provided in this specification will now be clearly and completely described in conjunction with the accompanying drawings. Those skilled in the art will be able to implement the embodiments of the invention provided in this specification based on these descriptions. Before describing the embodiments of the invention provided in this specification in conjunction with the accompanying drawings, it should be particularly noted that: The technical solutions and features provided in the embodiments of the invention provided in this specification, including the following description, can be combined with each other without conflict.
[0020] Furthermore, the embodiments of the inventions provided in this specification mentioned below are generally only a part of the embodiments of the inventions provided in this specification, and not all of them. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the inventions provided in this specification without creative effort should fall within the scope of protection of the embodiments of the inventions provided in this specification.
[0021] Regarding the terminology and units in the embodiments of the invention provided in this specification: The terms "comprising," "including," "having," and any variations thereof in the description, claims, and related parts of the embodiments of the invention provided in this specification are intended to cover non-exclusive inclusion. Furthermore, other relevant terms and units in the embodiments of the invention provided in this specification can be reasonably interpreted based on the relevant content of the embodiments of the invention provided in this specification.
[0022] Example 1
[0023] The preparation method of high residual chlorine adsorption activated carbon in this embodiment includes the following steps: (1) Carbonize the bamboo at 600°C for 3 hours in the absence of air, and then crush it to 150 mesh after cooling to obtain primary carbonized material. Weigh 100 parts by weight of the primary carbonized material for later use. The following component amounts are based on this.
[0024] Separately prepare an aqueous solution of L-lysine with a concentration of 10 wt%. The amount of this aqueous solution added is 25% (i.e., 25 parts by weight) of the mass of the primary carbonized material. Add ferrous gluconate (calculated as 1.5% of the mass of the primary carbonized material, i.e., 1.5 parts by weight of iron) to the aqueous solution and stir the mixture at 50°C for 45 minutes to obtain an amino acid-iron pre-reaction solution.
[0025] The pre-reaction liquid is mixed with 100 parts by weight of primary carbonized material, and then a binder and a pore-forming agent are added. After kneading and molding, a shaped green body is obtained. The binder is an aqueous solution of sodium carboxymethyl cellulose with a concentration of 3 wt%, and the amount is calculated based on the solute being 0.5% of the mass of the primary carbonized material. The pore-forming agent is sodium bicarbonate (particle size ≤ 48 micrometers, i.e., sieved through a 300-mesh sieve), and the amount is 5 parts by weight.
[0026] (2) Place the molded blank under air-isolated conditions and keep it at 700℃ for 60 minutes to complete the secondary carbonization and obtain the secondary carbonized material.
[0027] (3) The secondary carbonized material is activated at 900°C in a steam atmosphere for 120 minutes to obtain activated material.
[0028] (4) The activated material is rapidly cooled to below 200°C in a nitrogen atmosphere at a cooling rate of 200°C / min, and then naturally cooled to room temperature. After cooling, it is first acid-washed with 1 mol / L citric acid solution, and then washed with deionized water until the washing solution is neutral. After drying, high residual chlorine adsorption activated carbon is obtained.
[0029] The specific surface area of the high residual chlorine adsorption activated carbon in this embodiment was tested to be 1285.6 m². 2 / g, of which the microporous specific surface area is 892.3m². 2 / g, with a mesoporous specific surface area of 393.3m². 2 / g; iodine value 1253mg / g; half-dechlorination value 3.2cm; iron leaching amount below the detection limit (detection limit is 0.01mg / L).
[0030] Figure 1 This is the curve showing the change in residual chlorine concentration over time obtained from the static adsorption experiment in this embodiment. Figure 1 It can be seen that the residual chlorine concentration of the chlorinated water sample with an initial residual chlorine concentration of 50 mg / L decreased rapidly after contact with activated carbon, dropping to 17.8 mg / L within 10 minutes, and below 2.8 mg / L after 30 minutes. Adsorption equilibrium was reached after about 70 minutes, with an equilibrium concentration of about 0.8 mg / L. The calculated residual chlorine adsorption capacity was 49.2 mg / g, and the residual chlorine removal rate was 98.4%, indicating that the high residual chlorine adsorption activated carbon of the present invention has excellent static adsorption rate and extremely high residual chlorine removal capacity.
[0031] Figure 2 This is a curve showing the change in residual chlorine concentration in the effluent over operating time, obtained from the dynamic adsorption experiment in this embodiment. Figure 2 It can be seen that under the conditions of an influent residual chlorine concentration of 2.0 mg / L and a flow rate of 5 mL / min, after 120 hours of continuous operation, the effluent residual chlorine concentration remained stable at around 0.013 mg / L, which was always far below 0.5 mg / L (the national standard limit, which is the end of the service life). This indicates that the high residual chlorine adsorption activated carbon of the present invention has excellent adsorption life and stable effluent water quality under dynamic use conditions.
[0032] Example 2
[0033] Compared with Example 1, the preparation method of high residual chlorine adsorption activated carbon in this example is different in that: in step (1), the amino acid used is L-arginine, the aqueous solution concentration is 8wt%, and the amount used is 20% of the mass of the primary carbonization material; the organic acid iron salt used is iron ammonium citrate (calculated as 3% of the mass of the primary carbonization material based on iron element), and the pre-reaction condition is stirring at 40°C for 60 minutes.
[0034] Tests showed that the specific surface area of the high residual chlorine adsorption activated carbon in this embodiment is 1220.4 m². 2 / g, of which the microporous specific surface area is 858.6m² 2 / g, with a mesoporous specific surface area of 361.8m². 2 / g; iodine value 1195mg / g; half-dechlorination value 3.8cm; iron leaching amount below the detection limit.
[0035] Example 3
[0036] Compared with Example 1, the preparation method of high residual chlorine adsorption activated carbon in this example is different in that: in step (1), the amino acid used is L-histidine, the aqueous solution concentration is 4wt%, and the amount used is 30% of the mass of the primary carbonization material; the organic acid iron salt used is ferrous fumarate (calculated as 0.5% of the mass of the primary carbonization material based on iron element), and the pre-reaction condition is stirring at 60℃ for 30 minutes.
[0037] The specific surface area of the high residual chlorine adsorption activated carbon in this embodiment was tested to be 1252.8 m². 2 / g, of which the microporous specific surface area is 856.2m² 2 / g, with a mesoporous specific surface area of 396.6m². 2 / g; iodine value 1218mg / g; half-dechlorination value 3.6cm; iron leaching amount below the detection limit.
[0038] Example 4
[0039] Compared with Example 1, the difference in the preparation method of high residual chlorine adsorption activated carbon in this example is that in step (1), potassium bicarbonate is used as the pore-forming agent, and the amount added is 15% of the mass of the primary carbonization material.
[0040] The specific surface area of the high residual chlorine adsorption activated carbon in this embodiment was tested to be 1312.5 m². 2 / g, of which the microporous specific surface area is 868.4m² 2 / g, with a mesoporous specific surface area of 444.1m³. 2 / g; iodine value 1275mg / g; half-dechlorination value 3.5cm; residual chlorine adsorption capacity 48.6mg / g, residual chlorine removal rate 97.2%; iron leaching amount is below the detection limit.
[0041] Example 5
[0042] Compared with Example 1, the preparation method of high residual chlorine adsorption activated carbon in this example is different in that: in step (1), the binder is a starch solution (using corn starch) with a concentration of 8wt%, and the amount is calculated based on the solute being 3% of the mass of the primary carbonization material. The starch solution is prepared by adding corn starch to water to prepare an 8wt% slurry, heating it to 80℃ and stirring until completely gelatinized, and then cooling it to obtain the final product.
[0043] The specific surface area of the high residual chlorine adsorption activated carbon in this embodiment was tested to be 1238.2 m². 2 / g, of which the microporous specific surface area is 876.5m² 2 / g, with a mesoporous specific surface area of 361.7m². 2 / g; iodine value 1198mg / g; half-dechlorination value 3.7cm; iron leaching amount below the detection limit.
[0044] Example 6
[0045] Compared with Example 1, the preparation method of high residual chlorine adsorption activated carbon in this example is different in that: in step (2), the secondary carbonization temperature is 800℃ and the carbonization time is 30 minutes. In step (3), the steam activation temperature is 850℃ and the activation time is 180 minutes.
[0046] Tests showed that the specific surface area of the high residual chlorine adsorption activated carbon in this embodiment is 1265.3 m². 2 / g, of which the microporous specific surface area is 886.7m² 2 / g, with a mesoporous specific surface area of 378.6m². 2 / g; iodine value 1232mg / g; half-dechlorination value 3.5cm; iron leaching amount below the detection limit.
[0047] Example 7
[0048] Compared with Example 1, the preparation method of high residual chlorine adsorption activated carbon in this example is different in that: in step (2), the secondary carbonization temperature is 600℃ and the carbonization time is 90 minutes; in step (3), the steam activation temperature is 950℃ and the activation time is 60 minutes.
[0049] The specific surface area of the high residual chlorine adsorption activated carbon in this embodiment was tested to be 1278.4 m². 2 / g, of which the microporous specific surface area is 882.1m³. 2 / g, with a mesoporous specific surface area of 396.3m². 2 / g; iodine value 1245mg / g; half-dechlorination value 3.4cm; iron leaching amount below the detection limit.
[0050] Example 8
[0051] Compared with Example 1, the preparation method of high residual chlorine adsorption activated carbon in this example is different in that: in step (4), the rapid cooling rate is 50℃ / min and the cooling endpoint temperature is 300℃; the acid washing uses 0.1mol / L citric acid solution.
[0052] The specific surface area of the high residual chlorine adsorption activated carbon in this embodiment was tested to be 1270.2 m². 2 / g, of which the microporous specific surface area is 886.8m² 2 / g, with a mesoporous specific surface area of 383.4m³. 2 / g; iodine value 1235mg / g; half-dechlorination value 4.0cm; residual chlorine adsorption capacity 47.5mg / g, residual chlorine removal rate 95.0%; iron leaching amount 0.02mg / L.
[0053] Compare with Example 1 Compared with Example 1, the difference in the preparation method of activated carbon in this comparative example is that amino acids were not used in step (1), and organic acid iron salts were directly dissolved in water and then mixed with the primary carbonization material.
[0054] The specific surface area of the activated carbon in this control example was tested to be 1098.5 m². 2 / g, of which the microporous specific surface area is 782.4m³. 2 / g, with a mesoporous specific surface area of 316.1m³. 2 / g; iodine value 1052mg / g; half-dechlorination value 6.8cm; residual chlorine adsorption capacity 36.3mg / g; residual chlorine removal rate 72.6%; iron leaching amount 0.08mg / L.
[0055] Compare with Example 2 Compared with Example 1, the difference in the preparation method of activated carbon in this comparative example is that: organic acid iron salts were not used in step (1).
[0056] The specific surface area of the activated carbon in this control example was tested to be 1045.2 m². 2 / g, of which the microporous specific surface area is 778.6m² 2 / g, with a mesoporous specific surface area of 266.6m². 2 / g; iodine value 1018 mg / g; half-dechlorination value 6.2 cm; residual chlorine adsorption capacity 38.4 mg / g; residual chlorine removal rate 76.8%; iron leaching amount below detection limit. Compared with control example 1, it can be seen that the nitrogen-involved carbon defect sites themselves have catalytic reduction activity for residual chlorine, while iron without nitrogen coordination is only iron oxide particles, with limited catalytic activity.
[0057] Compare with Example 3 Compared with Example 1, the difference in the preparation method of activated carbon in this comparative example is that: in step (4), rapid cooling was not carried out, but the activated carbon was naturally cooled to room temperature after activation (cooling rate of about 5°C / minute).
[0058] The specific surface area of the activated carbon in this control example was tested to be 1252.4 m². 2 / g, of which the microporous specific surface area is 878.5m² 2 / g, with a mesoporous specific surface area of 373.9m². 2 / g; iodine value 1185mg / g; half-dechlorination value 5.5cm; residual chlorine adsorption capacity 41.4mg / g; residual chlorine removal rate 82.8%; iron leaching amount below detection limit.
[0059] Compare with Example 4 Compared with Example 1, the difference in the preparation method of activated carbon in this comparative example is that: in step (1), the organic acid iron salt was not added to the amino acid aqueous solution for pre-reaction, but the amino acid aqueous solution and ferrous gluconate powder were added separately to the carbonization material and mixed directly.
[0060] The specific surface area of the activated carbon in this control example was tested to be 1182.6 m². 2 / g, of which the microporous specific surface area is 842.3m². 2 / g, with a mesoporous specific surface area of 340.3m². 2 / g; iodine value 1125mg / g; half-dechlorination value 5.0cm; residual chlorine adsorption capacity 42.1mg / g; residual chlorine removal rate 84.2%; iron leaching amount 0.05mg / L.
[0061] The high residual chlorine adsorption activated carbon of the present invention was prepared by the preparation method described in any of the above embodiments.
[0062] The water purification filter element of the present invention is filled with high residual chlorine adsorption activated carbon prepared by the preparation method described in any of the above embodiments, which may be, but is not limited to, any one of the particle-filled column structure, sintered rod structure, and compressed carbon block structure.
[0063] The testing methods for the above performance parameters are as follows: 1. Specific surface area test: The sample was vacuum degassed at 300℃ for 6 hours to remove adsorbed moisture and impurities from the surface. Then, the nitrogen adsorption-desorption isotherm was measured at liquid nitrogen temperature (77K) using a fully automated specific surface area and pore size analyzer. The total specific surface area was calculated using the BET (Brunauer-Emmett-Teller) multi-point method, the microporous specific surface area was obtained using the t-plot method, and the mesoporous specific surface area was obtained by subtracting the microporous specific surface area from the total specific surface area.
[0064] 2. Iodine value testing shall be conducted in accordance with GB / T 12496.8-2015.
[0065] 3. The half-dechlorination value shall be tested according to the half-dechlorination value test method in MT / T1155-2011.
[0066] 4. The residual chlorine adsorption capacity and residual chlorine removal rate were tested using a static adsorption experiment, specifically as follows: A chlorinated water sample with a residual chlorine concentration of 50 mg / L and a pH of 7.0 ± 0.1 was prepared using deionized water and sodium hypochlorite. 30 g of activated carbon was placed in a polyethylene container containing 30 L of the chlorinated water sample, and the mixture was continuously stirred at 150 rpm under a constant temperature of 25 ± 1 °C. Every 10 minutes, 5 mL of the supernatant was collected, filtered through a 0.45 μm filter membrane, and the residual chlorine concentration was measured using the DPD spectrophotometric method until adsorption equilibrium was reached (the concentration change at three consecutive adjacent time points was less than 5%). The residual chlorine adsorption capacity and residual chlorine removal rate were calculated using the following formulas: Residual chlorine adsorption capacity = (C0 - Ce) × V / m; Residual chlorine removal rate = (C0 - Ce) / C0 × 100%; In the formula, C0 is the residual chlorine concentration of the chlorine-containing water sample, C0 = 50 mg / L; Ce is the residual chlorine concentration at adsorption equilibrium; V is the volume of the chlorine-containing water sample, V = 30 L; and m is the amount of activated carbon loaded, m = 30 g.
[0067] 5. The adsorption lifetime was tested using a dynamic adsorption experiment. Specifically, a stock solution with a residual chlorine concentration of 2.0 mg / L and a pH of 7.0 ± 0.1 was prepared using tap water and sodium hypochlorite. 30 g of activated carbon was packed into a transparent PVC filter column with an inner diameter of 4 cm and a height of 10 cm. First, pure water was introduced through a peristaltic pump for 10 minutes to remove air bubbles from the carbon layer. Then, the stock solution was introduced at a flow rate of 5 mL / min. 5 mL of the permeate water was sampled every hour, and the residual chlorine in the water was detected using the DPD method. The time when the residual chlorine concentration in the effluent reached 0.5 mg / L and the corresponding cumulative water volume were taken as the endpoint of the adsorption lifetime.
[0068] 6. Iron leaching test: Take 1g of activated carbon and soak it in 1000mL of deionized water. After shaking and soaking for 24 hours at 25℃, determine the iron ion concentration in the water according to GB / T12496.22-1999.
[0069] The embodiments of the invention provided in this specification have been described above. Those skilled in the art will be able to implement the embodiments of the invention provided in this specification based on these descriptions. All other preferred embodiments and implementations obtained by those skilled in the art based on the above description of the embodiments of the invention provided in this specification without inventive effort should fall within the protection scope of the embodiments of the invention provided in this specification.
Claims
1. A method for preparing high residual chlorine adsorption activated carbon, characterized in that, Includes the following steps: (1) The primary carbonized material is mixed with amino acids, organic iron salts, binders and pore-forming agents and kneaded to form a molded body; the organic iron salts are added to the aqueous solution of the amino acids in advance, and stirred and reacted at 40-60℃ for 30-60 minutes before being mixed with the primary carbonized material. (2) The shaped blank is subjected to secondary carbonization to obtain secondary carbonized material; (3) The secondary carbonized material is activated by steam to obtain activated material; (4) The activated material is rapidly cooled in an inert atmosphere, and then washed and dried to obtain the high residual chlorine adsorption activated carbon; wherein the inert atmosphere is a nitrogen atmosphere, the rapid cooling rate is 50-200℃ / min, and the cooling endpoint temperature is ≤300℃.
2. The preparation method according to claim 1, characterized in that, The primary carbonized material is obtained by carbonizing bamboo under air-isolated conditions and then crushing it. The carbonization temperature is 500-650℃, the carbonization time is 2-4 hours, and the particle size is 100-200 mesh.
3. The preparation method according to claim 1, characterized in that, The amino acid is selected from at least one of L-lysine, L-arginine, and L-histidine; the organic acid ferric salt is selected from at least one of ferrous gluconate, ferric ammonium citrate, and ferrous fumarate.
4. The preparation method according to claim 3, characterized in that, The concentration of amino acids in the aqueous solution is 4-10 wt%, and the amount of aqueous solution added is 20-30% of the mass of the primary carbonized material; the amount of organic acid iron salt added is calculated as 0.5-3% of the mass of the primary carbonized material based on iron element.
5. The preparation method according to claim 1, characterized in that, The binder is selected from at least one of starch solution, sodium carboxymethyl cellulose solution and sodium alginate solution; the amount of binder added is calculated as 0.5-3% of the mass of the primary carbonized material.
6. The preparation method according to claim 1, characterized in that, The pore-forming agent is a bicarbonate that decomposes upon heating to produce gas, selected from at least one of sodium bicarbonate and potassium bicarbonate; the particle size of the pore-forming agent is no greater than 48 micrometers; the amount of the pore-forming agent added is 5-15% of the mass of the primary carbonized material.
7. The preparation method according to claim 1, characterized in that, In step (2), the secondary carbonization is carried out under air-isolated conditions, with a carbonization temperature of 600-800℃ and a carbonization time of 30-90 minutes; In step (3), the temperature for steam activation is 850-950℃ and the activation time is 60-180 minutes.
8. The preparation method according to claim 1, characterized in that, In step (4), acid washing is performed first, followed by water washing. The acid washing uses a 0.1-1 mol / L citric acid solution.
9. High residual chlorine adsorption activated carbon, characterized in that: It is prepared by the preparation method according to any one of claims 1-8.
10. A water purification filter element, characterized in that: It is filled with the high residual chlorine adsorption activated carbon as described in claim 9.
Citation Information
Patent Citations
Preparation method of modified activated carbon for removing organic malodorous gas and modified activated carbon
CN117244526A
Drinking water difunctional filtering carbon material as well as preparation method and application thereof
CN121731866A